Etiology of oak decline in Spain - Gallego, F J; de Algaba, A Perez; Fernandez-Escobar, R (European Journal of Forest Pathology, 1999)
In different areas of Extremadura, Western Spain, soil samples were taken at the bottom of holm oak (Quercus ilex) trees that were showing decline symptoms. Half of each sample was sterilized, and acorns were sown in both sterilized and nonsterilized soil samples. The resulting seedlings were used as baits for the isolation of fungi. Seedlings growing on the natural, nonsterilized substrate were characterized by having a lower vegetative growth than the ones growing on the sterilized soil samples, and most of them died. Phytophthora dnnamomi was consistently isolated from their roots. Fusarium oxysporum was also isolated as well as different species of Pythium, although to a lesser extent. Pathogenicity tests were performed on holm oak seedlings with five different isolates of P. chinnamomi, with F. oxysporum, Pythium and with a mixture of the three fungi. All the inoculated seedlings with P. chinnamomi developed root rot and grew slowly, and 35.7% of them died up to the end of the experiments. P. chinnamomi was consistently isolated from their roots, indicating that this fungus is the causal agent of holm oak decline. However, F. oxysporum caused similar symptoms on oak seedlings as P. chinnamomi, and was isolated also from the roots, although its frequency was lower than that of. P. cinnamomi.
Keywords: Holm oak; Oak decline; Pathogenicity; Phytophthora cinnamomi (PG)

Treatment of oak decline using pressurized injection capsules of antifungal materials - Fernandez-Escobar, R; Gallego, F J; Benlloch, M; Membrillo, J; Infante, J; de Algaba, A Perez (European Journal of Forest Pathology, 1999)
Quercus ilex and Quercus suber trees growing at several sites in Extremadura, Western Spain, that were showing symptoms of oak decline were injected with potassium phosphonate, quinosol or carbendazim using a low-pressure method of trunk injection composed of a pressurized capsule system. A team of four people injected between 120 and 189 trees per day, depending upon the density of the undergrowth vegetation. This labour cost represented, approximately, 15–20% of the total cost of the treatment. The potassium phosphonate-injected trees showed a significant improvement in vegetative growth within 2 years of the injection treatment, and they also showed some recovery from the decline symptoms during the third year. Only one injection treatment of an average of 3.5 capsules (corresponding to 24.5 g phosphonic acid) per tree of approximately 36 cm in diameter, was necessary to reduce the disease severity significantly. Indirectly, these results corroborate the implication of Phytophthora cinnamomi in oak decline within Spanish Quercus woodlands.
Keywords: Oak decline; phosphonic acid; trunk injections (PG)